The Ethics of Clothing in Islam - Nor Hayati Bt Che Abdul Ghani (Kolej Universiti Islam Malaysia, 2011)
This research project discusses about the ethics of clothing in Islam. Clothes is one of the important elements in the human daily life. In Islamic perspective, clothes is something that are used to cover the aurah and the part of bodies. In this research, the writer focus on the ethics of wearing accordance to a true teaching of Islam and what related with it. The main objective of this research is to give a detail exposure about the conditions and rules in wearing as its have been fixed and taught by Islam. In this research also, the writer have used several of methods such as library research and Internet. This research consists of 5 chapters. In first chapter, the writer discuss about the proposal and in chapter two, about the ethics or adab of clothing in Islam. In chapter three the writer discuss about the conditions of clothing in Islam, in chapter fourth mention about the issues of clothing among Muslims and lastly the conclusion of this research. In conclusion, the writer concludes that Islam has their own adab and conditions in clothing that must be follows by Muslim and Muslimat.